2021
DOI: 10.1186/s12889-021-11587-x
|View full text |Cite
|
Sign up to set email alerts
|

Scrutinize of healthy school canteen policy in Iran’s primary schools: a mixed method study

Abstract: Background Schools provide an opportunity for developing strategies to create healthy food environments for children. The present study aimed to analyze the Healthy School Canteen (HSC) policy and identify challenges of its implementation to improve the school food environment in Iran. Methods This mixed method study included two qualitative and quantitative phases. In the qualitative phase, triangulation approach was applied by using semi-structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 61 publications
0
19
0
Order By: Relevance
“…There are few countries that have conducted monitoring and evaluation activities. In Iran, food items available in primary schools’ canteens in Tehran were evaluated [ 176 ], and compliance with the guidelines was assessed by comparing nutrient content of food items (TS, AS and non-sugar sweeteners) with the WHO EMR nutrient profile model [ 226 ] and Iran Healthy School Canteen Guideline [ 175 ]. The findings showed that 9.2% of chocolates, sugar confectionery and desserts that were available in the school canteens, as well as 15.7% of beverages and 45.2% of cakes, sweet biscuits and pastries, are not permitted based on the WHO EMR model [ 176 , 226 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are few countries that have conducted monitoring and evaluation activities. In Iran, food items available in primary schools’ canteens in Tehran were evaluated [ 176 ], and compliance with the guidelines was assessed by comparing nutrient content of food items (TS, AS and non-sugar sweeteners) with the WHO EMR nutrient profile model [ 226 ] and Iran Healthy School Canteen Guideline [ 175 ]. The findings showed that 9.2% of chocolates, sugar confectionery and desserts that were available in the school canteens, as well as 15.7% of beverages and 45.2% of cakes, sweet biscuits and pastries, are not permitted based on the WHO EMR model [ 176 , 226 ].…”
Section: Resultsmentioning
confidence: 99%
“…In Iran, food items available in primary schools’ canteens in Tehran were evaluated [ 176 ], and compliance with the guidelines was assessed by comparing nutrient content of food items (TS, AS and non-sugar sweeteners) with the WHO EMR nutrient profile model [ 226 ] and Iran Healthy School Canteen Guideline [ 175 ]. The findings showed that 9.2% of chocolates, sugar confectionery and desserts that were available in the school canteens, as well as 15.7% of beverages and 45.2% of cakes, sweet biscuits and pastries, are not permitted based on the WHO EMR model [ 176 , 226 ]. Similarly, 13.7% of chocolates, sugar confectionery and desserts found in the canteens, 19.7% of beverages and 28.8% of cakes, sweet biscuits and pastries are not permitted based on the national guideline [ 175 , 176 ].…”
Section: Resultsmentioning
confidence: 99%
“…The school canteen is an integral aspect of the eating environment at the school. It is vital in increasing the quality of school eating to provide a healthy atmosphere for youngsters [35]. Because dangers from many sources may cause contamination throughout the food preparation and distribution phases and eventually contribute to the development of FDS [36], quality management of school catering is essential.…”
Section: School Canteenmentioning
confidence: 99%
“…Although several efforts in the area of nutrition have been made for the prevention and management of hypertension in developing countries such as Iran, populationbased studies have shown that control and preventive measures for high blood pressure levels are far from the optimal level [56]. Evidence indicated that the formulation of these policies faces barriers and challenges that restrict achieving the desired effects on the intended outcomes [57][58][59]. There are several possible reasons for the failure and ineffectiveness of these programs, including a focus on single criteria for priority setting (such as effectiveness, cost-effectiveness, etc.)…”
Section: Open Accessmentioning
confidence: 99%
“…For example, in 2014, the Ministry of Health, Treatment and Medical Education (MoHME) formulated the national guidelines for Healthy School Canteen (HSC), based on the available evidence regarding the high consumption of unhealthy and nutrient-poor foods by children and availability of such foods in schools [62]. Based on the HSC guideline, all schools in Iran should provide healthy foods and drink choices in their canteens and limit selling unhealthy items [57,62]. Two recent studies evaluated the implementation of this bylaw and provided evidence on the failure to achieve the desired result [63,64].…”
Section: Open Accessmentioning
confidence: 99%